ATP and cough reflex hypersensitivity: a confusion of goals?. Issue 1 (6th July 2017) - Belvisi, Maria G.; Smith, Jaclyn A.
The term "cough hypersensitivity syndrome" (CHS) has been proposed by a European Respiratory Society Task Force as a clinical syndrome characterised by troublesome coughing often triggered by low levels of thermal, mechanical or chemical exposure, in patients presenting with chronic cough [1]. There are no agreed clinical criteria defining this syndrome or diagnostic tests to confirm its presence. However, it is often assumed that this syndrome must be linked to a hypersensitivity of the vagal afferent nerves and an intrinsic defect in the nerves themselves, which may not be the case [2]. The paper by Fowles et al . [3] describes a tussive challenge study with ATP and AMP in healthy volunteers and unselected patients attending a cough clinic, demonstrating the greater potency of ATP versus AMP, and that chronic cough patients had a greater cough response at lower concentrations of ATP. The degree of hypersensitivity demonstrated in chronic cough patients did not appear to be greater in magnitude than seen previously with capsaicin challenge (the only other example where an intervention against a specific challenge agent has been tested) [4–6]. However, a TRPV1 receptor antagonist did not impact on cough in this patient group despite a greater sensitivity to capsaicin challenge [6]. The authors have concluded, therefore, that 1) a similar shift in sensitivity in the ATP challenge does not explain the efficacy of the P2X3 antagonist (AF-219/MK-7264) and that 2) it is not a peripheral response to ATP that underlies the increased coughing in these patients. The term "cough hypersensitivity syndrome" describes exaggerated cough but not necessarily the mechanisms involved http://ow.ly/Wk0n30bWmAy